Using online blogs to explore positive outcomes after burn injuries - Garbett, Kirsty; Harcourt, Diana; Buchanan, Heather (SAGE Publishing, 2017)
This study uses blog analysis, a new and novel technique, to explore the positive outcomes experienced by burn survivors. This study examined 10 burn survivor blogs to offer a unique, longitudinal insight into burn survivor recovery. Using thematic analysis, three themes emerged: shift in self-perception, enhanced relationships and a change in life outlook. Many of these themes contained stories and experiences unique to a traumatic burn injury, suggesting that standardised trauma scales are not effectively measuring the impact of a burn in this population. Reflections on blog analysis are discussed, along with a recommendation that health researchers utilise the vast amount of data available from online blogs.